2020
DOI: 10.1186/s13293-020-0283-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and neurotoxic outcomes of androgens and estrogens in an oxidative stress environment

Abstract: Background: The role of sex hormones on cellular function is unclear. Studies show androgens and estrogens are protective in the CNS, whereas other studies found no effects or damaging effects. Furthermore, sex differences have been observed in multiple oxidative stress-associated CNS disorders, such as Alzheimer's disease, depression, and Parkinson's disease. The goal of this study is to examine the relationship between sex hormones (i.e., androgens and estrogens) and oxidative stress on cell viability. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 139 publications
0
14
0
1
Order By: Relevance
“…Together, these studies and others ( Shansky et al, 2004 , 2009 ) indicate that estrogen is not universally protective, and the interaction of stress and estrogen on memory is complex. Hormone levels, whether these were endogenous or exogenous, delivery regimen, period of deprivation, stressor type, memory task, time of day, and the underlying brain regions and networks are all crucial in interpreting the interactions between estrogen, stress, and memory ( Holmes et al, 2002 ; McLaughlin et al, 2008 ; Barha et al, 2010 ; Babb et al, 2014 ; Korol and Pisani, 2015 ; Graham and Scott, 2018 ; Duong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these studies and others ( Shansky et al, 2004 , 2009 ) indicate that estrogen is not universally protective, and the interaction of stress and estrogen on memory is complex. Hormone levels, whether these were endogenous or exogenous, delivery regimen, period of deprivation, stressor type, memory task, time of day, and the underlying brain regions and networks are all crucial in interpreting the interactions between estrogen, stress, and memory ( Holmes et al, 2002 ; McLaughlin et al, 2008 ; Barha et al, 2010 ; Babb et al, 2014 ; Korol and Pisani, 2015 ; Graham and Scott, 2018 ; Duong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the unconjugated steroids, the reactions between DHEA and androst-5-ene-3β,17β-diol, androstenedione and testosterone and estrone and estradiol are preferentially conducted in the reductase direction (Purohit and Foster, 2012;Mostaghel, 2013). generally act as neuroprotective substances (Fargo et al, 2009;Spence and Voskuhl, 2012;Duong et al, 2020;Yang et al, 2020) and promote neurogenesis and neuro-regeneration (Pillerová et al, 2021;Azcoitia et al, 2019). These processes in the brain take place through classical nuclear steroid receptors (estrogen receptor α and β-ERα and ERβ, androgen receptor-AR, progesterone receptor-PR), non-classical membraneassociated steroid receptors (AR, ERα, ERβ) and transmembrane receptors (zinc transporter protein 9, G protein coupled estrogen receptor 1) (Pillerová et al, 2021).…”
Section: Unconjugated Steroidsmentioning
confidence: 99%
“…Particularly E2 exert pleiotropic effects there, facilitating learning and memory ( Frick, 2015 ; Sun et al, 2019 ; Luine and Frankfurt, 2012 ; Tozzi et al, 2020 ; Dieni et al, 2020 ), as well as influencing emotional ( Altemus, 2019 ) and sexual behavior ( Diotel et al, 2018 ). They generally act as neuroprotective substances ( Fargo et al, 2009 ; Spence and Voskuhl, 2012 ; Duong et al, 2020 ; Yang et al, 2020 ) and promote neurogenesis and neuro-regeneration ( Pillerová et al, 2021 ; Azcoitia et al, 2019 ). These processes in the brain take place through classical nuclear steroid receptors (estrogen receptor α and β-ERα and ERβ, androgen receptor-AR, progesterone receptor-PR), non-classical membrane-associated steroid receptors (AR, ERα, ERβ) and transmembrane receptors (zinc transporter protein 9, G protein coupled estrogen receptor 1) ( Pillerová et al, 2021 ).…”
Section: Unconjugated Steroidsmentioning
confidence: 99%
“… 60 In a dopaminergic cell line (N27 cells), flutamide inhibited testosterone-induced apoptosis, 61 and apoptosis effect of testosterone was recently reported to be mediated by a membrane androgen receptor in N27 cells. 62 A case report showed that low-dose cyproterone acetate treatment reduced sexual acting out in a man with PD and dementia without relevant side effects. 63 As reviewed above, there are limited studies with the androgen receptor inhibitors in PD, whereas the 5α-reductase inhibitors have led to recent interesting findings.…”
Section: Antiandrogenic Therapies In Pdmentioning
confidence: 99%